Preparation method of degradable spunlace non-woven fabric capable of being bonded through ultrasonic waves
The use of skin-core bicomponent PLA/PBS fiber with ultrasonic bonding addresses the bonding challenges of cellulose fibers, creating a high-strength, low-cost, and environmentally friendly non-woven fabric.
Patent Information
- Application Number
- CN202411324325.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-09-23
AI Technical Summary
Cellulose fibers lack bonding ability, requiring glue or manual stitching, which increases production costs and introduces pollution, limiting their widespread application in non-woven fabrics.
Introduce skin-core bicomponent PLA/PBS fiber with ultrasonic bonding characteristics to bond cellulose fibers effectively, using low melting point polybutylene succinate (PBS) and high melting point polylactic acid (PLA) to form a degradable spunlace non-woven fabric.
The method produces a non-woven fabric with high strength and low labor costs, reducing environmental pollution and enhancing mechanical properties through improved adhesion and flexibility.
Smart Images

Figure BDA0005054965450000191 
Figure BDA0005054965450000201
Abstract
Description
Technical Field
[0001] The invention provides a method for preparing a degradable spunlace nonwoven fabric capable of ultrasonic bonding, and relates to the technical field of nonwoven fabric preparation. Background Art
[0002] With the improvement of global environmental awareness and the demand for sustainable resource utilization, the application of biodegradable materials is gaining increasing attention. As an important textile material, non-woven fabrics are widely used in many fields such as medicine, hygiene, packaging, agriculture, etc. due to their low cost, fast production speed and versatility. However, most non-woven fabric materials are still made of non-degradable synthetic polymers such as polypropylene and polyester. These synthetic materials are difficult to degrade naturally in the environment, causing serious plastic pollution problems and bringing long-term negative impacts to the ecosystem.
[0003] In order to deal with this problem, cellulose fiber has received more and more attention as a renewable resource with great potential. Cellulose fiber is not only widely available and low-cost, but also has good biodegradability and renewability, making it an ideal material to replace traditional petroleum-based fibers (such as polypropylene and polyester). By using cellulose fiber to prepare non-woven products, we can reduce dependence on non-degradable plastics, thereby reducing environmental pollution, promoting green and low-carbon development, and enhancing the market's environmental competitiveness.
[0004] However, the current application of cellulose fibers in the production of nonwoven fabrics faces some technical challenges. Since cellulose fibers themselves lack bonding ability, they need to be bonded with glue or manually stitched to prepare nonwoven fabrics, which not only increases production costs, but may also introduce pollution problems caused by chemical adhesives. This limits the widespread application of cellulose fibers in efficient and environmentally friendly production. Therefore, the development of new cellulose fiber bonding technologies, such as hydroentanglement, thermal bonding, or enhanced bonding properties through modified fibers, has become a hot topic and direction of current research. The introduction of these innovative processes will further enhance the performance and market application potential of cellulose-based nonwoven fabrics, and provide a greener and more sustainable solution to the problem of plastic pollution. Through technological innovation and market promotion, cellulose fibers are expected to play a more important role in the future nonwoven fabric industry and promote the global textile industry to develop in a more environmentally friendly and sustainable direction. Summary of the invention
[0005] In order to solve the problem that cellulose fibers cannot be effectively bonded, this study proposes an innovative solution: by introducing the skin-core bicomponent PLA / PBS fiber, using its ultrasonic bonding characteristics, cellulose fibers and bio-based fibers can be effectively bonded together to form a new type of non-woven fabric with high strength, low labor cost, and ultrasonic bonding. The specific solution is as follows:
[0006] A method for preparing a degradable spunlace nonwoven fabric capable of ultrasonic bonding comprises the following steps:
[0007] S1, taking low melting point polybutylene succinate (PBS) and polyphosphate (PPE), and high melting point polylactic acid (PLA) pellets for drying;
[0008] S2, taking low melting point polybutylene succinate (PBS) and polyphosphate (PPE) and tributyl citrate (TBC) and mixing them evenly to obtain material A;
[0009] S3, melting material A and high melting point polylactic acid (PLA) by two screws of a bicomponent spinning machine respectively, and spinning the two melts through a sheath-core spinning assembly to obtain a sheath-core PLA / PBS composite fiber;
[0010] S4. The obtained core-sheath PLA / PBS composite fibers are dried and cut into core-sheath PLA / PBS composite short fibers; the obtained core-sheath PLA / PBS composite short fibers are mixed with cellulose fibers and formed into a web using a web forming machine to obtain a fiber web, the obtained fiber web is treated with a high-pressure water spunlace machine to obtain a water-spunlace fiber web, and then dried to obtain a degradable water-spunlace non-woven fabric.
[0011] Preferably, the drying in step S1 is performed by vacuum drying at 45-65° C. for 8-12 hours. After drying, the moisture content of the low-melting-point polybutylene succinate (PBS), polyphosphate ester (PPE) and high-melting-point polylactic acid (PLA) pellets is less than 50 PPm.
[0012] Preferably, the low-melting-point polybutylene succinate in step S1 has a melting point of 105-130°C, and the high-melting-point polylactic acid has a melting point of 155°C-175°C.
[0013] Preferably, in the material A in step S2, the mass ratio of low melting point polybutylene succinate to polyphosphate and tributyl citrate is (80-100):(10-15):(3-5).
[0014] Preferably, the mass ratio of the high melting point polylactic acid in step S3 to the low melting point polybutylene succinate in material A is (10-90):(10-90).
[0015] Preferably, in step S3, the melting temperature of material A is controlled at 110-135°C; and the melting temperature of the high melting point polylactic acid is controlled at 160-180°C.
[0016] Preferably, in the spinning of step S3, the spinning temperature is 155-170° C., the winding speed is 700-1300 m / min; the drawing temperature is 60-90° C., and the drawing multiple is 2.5-4.5 times.
[0017] Preferably, the drying in step S4 is performed by hot air drying at 80-130° C., and the sheath-core PLA / PBS composite short fibers have a length of 3-100 mm.
[0018] Preferably, the cellulose fiber in step S4 includes one or more of viscose fiber, cotton, linen, bamboo fiber, and regenerated cellulose fiber.
[0019] Preferably, the cellulose fibers in step S4 have a length of 30-50 mm.
[0020] Preferably, the mass ratio of the core-sheath PLA / PBS composite short fibers to the cellulose fibers in step S4 is (1.25-7):(3-5).
[0021] Preferably, the web forming in step S4 is performed by airflow forming, and the airflow intensity is 0.5-1.0 m / s.
[0022] Preferably, in step S4, the pressure of the spunlace is 80-150 bar, the number of spunlaces is 2-4 times, and the speed of the fiber web passing through the spunlace machine is 10-30 m / min; and the drying is performed by hot air drying at a temperature of 80-100°C.
[0023] The beneficial effects of the present invention are as follows:
[0024] The present invention introduces the skin-core two-component PLA / PBS fiber and utilizes its ultrasonic bonding characteristics to effectively bond cellulose fiber and bio-based fiber together to form a new type of non-woven fabric with high strength, low labor cost and ultrasonic bonding.
[0025] The non-woven fabric uses the characteristics of PBS, which has a much lower melting point than conventional PLA and stronger adhesion, to increase the adhesion between PLA / PBS fibers and cellulose fibers, thereby inhibiting the occurrence of non-woven fabric fuzzing. Secondly, due to the good flexibility of PBS, the PLA / PBS composite fiber has a good soft touch, which helps to reduce the friction between electronic devices and non-woven packaging.
[0026] In addition, in the molten state, the viscosity and fluidity of PLA and PBS need to be coordinated to a certain extent, otherwise the stretching and winding behaviors of the two materials will be inconsistent during the spinning process, affecting the integrity and uniformity of the core-skin structure. During the stretching process, the PBS skin layer is overstretched, while the PLA core layer is understretched, which ultimately affects the mechanical properties and appearance of the fiber; during the winding and drafting process, the core layer and the skin layer materials need to have a certain mechanical property matching. The mechanical property difference between PLA and PBS is too large, and peeling or interface slippage between the core layer and the skin layer will occur during winding and drafting, resulting in a decrease in the overall strength of the fiber, especially when PBS is used as the skin layer, cracks or fractures will occur during the spinning process; although PLA and PBS are respectively used as the core layer and skin layer of the skin-core structure, the interface interaction between them is still very important during the spinning process. It is difficult for traditional methods to ensure good adhesion of the interface, and the skin layer peels or fluffs during drafting and subsequent processing. In our research and development process, we found that simply using the traditional control from the perspective of melting temperature cannot solve the above-mentioned problems existing in the skin-core two-component PLA / PBS fiber of the present invention. The present invention solves the above-mentioned problems by adding two special components to PBS. Thus, the mechanical properties and appearance of the nonwoven fabric are improved as a whole. In addition, we found that after adding the above two special components to the sheath-core bicomponent fiber, the ultrasonic bonding performance of the obtained nonwoven fabric is also improved.
[0027] Therefore, the sheath-core PLA / PBS fiber and cellulose fiber nonwoven fabric material of the present invention has important significance and application prospects in terms of environmental protection, sustainable utilization of resources and cost reduction. DETAILED DESCRIPTION
[0028] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0029] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.
[0030] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are purchased from commercial channels unless otherwise specified.
[0031] Preparation of a degradable spunlace nonwoven fabric capable of ultrasonic bonding:
[0032] S1, taking low melting point polybutylene succinate (PBS) and polyphosphate (PPE), and high melting point polylactic acid (PLA) pellets for drying;
[0033] S2, taking low melting point polybutylene succinate (PBS) and polyphosphate (PPE) and tributyl citrate (TBC) and mixing them evenly to obtain material A;
[0034] S3, melting material A and high melting point polylactic acid (PLA) by two screws of a bicomponent spinning machine respectively, and spinning the two melts through a sheath-core spinning assembly to obtain a sheath-core PLA / PBS composite fiber;
[0035] S4. The obtained core-sheath PLA / PBS composite fibers are dried and cut into core-sheath PLA / PBS composite short fibers; the obtained core-sheath PLA / PBS composite short fibers are mixed with cellulose fibers and formed into a web using a web forming machine to obtain a fiber web, the obtained fiber web is treated with a high-pressure water spunlace machine to obtain a water-spunlace fiber web, and then dried to obtain a degradable water-spunlace non-woven fabric.
[0036] The drying in step S1 is performed by vacuum drying at 45-65° C. for 8-12 hours. After drying, the moisture content of the low-melting-point polybutylene succinate (PBS), polyphosphate ester (PPE) and high-melting-point polylactic acid (PLA) pellets is less than 50 PPm.
[0037] In step S1, the low-melting-point polybutylene succinate has a melting point of 105-130°C, and the high-melting-point polylactic acid has a melting point of 155-175°C.
[0038] In the material A described in step S2, the mass ratio of low melting point polybutylene succinate to polyphosphate and tributyl citrate is (80-100):(10-15):(3-5).
[0039] The mass ratio of the high melting point polylactic acid in step S3 to the low melting point polybutylene succinate in material A is (10-90):(10-90).
[0040] In step S3, the melting temperature of material A is controlled at 110-135°C; the melting temperature of the high melting point polylactic acid is controlled at 160-180°C.
[0041] In step S3, the spinning temperature is 155-170° C., the winding speed is 700-1300 m / min; the drawing temperature is 60-90° C., and the drawing multiple is 2.5-4.5 times.
[0042] The drying in step S4 is performed by hot air drying at 80-130° C., and the length of the core-skin PLA / PBS composite short fibers is 3-100 mm.
[0043] The cellulose fibers in step S4 include one or more of viscose fibers, cotton, linen, bamboo fibers, and regenerated cellulose fibers.
[0044] The cellulose fibers in step S4 have a length of 30-50 mm.
[0045] The mass ratio of the core-skin PLA / PBS composite short fibers to the cellulose fibers in step S4 is (1.25-7):(3-5).
[0046] The web forming in step S4 is performed by airflow forming, and the airflow intensity is 0.5-1.0 m / s.
[0047] In step S4, the spunlace is performed at a pressure of 80-150 bar, the number of spunlaces is 2-4 times, and the speed at which the fiber web passes through the spunlace machine is 10-30 m / min; and the drying is performed by hot air drying at a temperature of 80-100°C.
[0048] Example 1 Preparation of a degradable spunlace nonwoven fabric capable of ultrasonic bonding:
[0049] S1, taking low melting point polybutylene succinate (PBS) and polyphosphate (PPE), and high melting point polylactic acid (PLA) pellets for drying;
[0050] S2, taking low melting point polybutylene succinate (PBS) and polyphosphate (PPE) and tributyl citrate (TBC) and mixing them evenly to obtain material A;
[0051] S3, melting material A and high melting point polylactic acid (PLA) by two screws of a bicomponent spinning machine respectively, and spinning the two melts through a sheath-core spinning assembly to obtain a sheath-core PLA / PBS composite fiber;
[0052] S4. The obtained core-sheath PLA / PBS composite fibers are dried and cut into core-sheath PLA / PBS composite short fibers; the obtained core-sheath PLA / PBS composite short fibers are mixed with cellulose fibers and formed into a web using a web forming machine to obtain a fiber web, the obtained fiber web is treated with a high-pressure water spunlace machine to obtain a water-spunlace fiber web, and then dried to obtain a degradable water-spunlace non-woven fabric.
[0053] The drying in step S1 is performed by vacuum drying at 45° C. for 12 hours. After drying, the moisture content of the low-melting-point polybutylene succinate (PBS), polyphosphate ester (PPE) and high-melting-point polylactic acid (PLA) pellets is less than 50 PPm.
[0054] In step S1, the low-melting-point polybutylene succinate has a melting point of 105-130°C, and the high-melting-point polylactic acid has a melting point of 155-175°C.
[0055] In the material A of step S2, the mass ratio of low melting point polybutylene succinate to polyphosphate and tributyl citrate is 100:10:3.
[0056] The mass ratio of the high melting point polylactic acid in step S3 to the low melting point polybutylene succinate in material A is 90:10.
[0057] In step S3, the melting temperature of material A is controlled at 110°C; the melting temperature of the high melting point polylactic acid is controlled at 160°C.
[0058] In step S3, the spinning temperature is 155° C. and the winding speed is 700 m / min; the drawing temperature is 60° C. and the drawing multiple is 2.5 times.
[0059] In step S4, the drying is performed at 80° C. with hot air, and the sheath-core PLA / PBS composite short fibers have a length of 30 mm.
[0060] The cellulose fibers in step S4 include cotton fibers.
[0061] The cellulose fibers in step S4 have a fineness of 1.5-4.5 tex and a length of 30 mm.
[0062] The mass ratio of the core-sheath PLA / PBS composite short fibers to the cellulose fibers in step S4 is 7:3.
[0063] The web forming in step S4 is performed by airflow forming with an airflow intensity of 0.5 m / s.
[0064] In step S4, the spunlace is performed at a pressure of 80 bar, the number of spunlaces is 2, and the speed at which the fiber web passes through the spunlace machine is 10 m / min; and the drying is performed by hot air drying at a temperature of 80°C.
[0065] Example 2 Preparation of a degradable spunlace nonwoven fabric capable of ultrasonic bonding:
[0066] S1, taking low melting point polybutylene succinate (PBS) and polyphosphate (PPE), and high melting point polylactic acid (PLA) pellets for drying;
[0067] S2, taking low melting point polybutylene succinate (PBS) and polyphosphate (PPE) and tributyl citrate (TBC) and mixing them evenly to obtain material A;
[0068] S3, melting material A and high melting point polylactic acid (PLA) by two screws of a bicomponent spinning machine respectively, and spinning the two melts through a sheath-core spinning assembly to obtain a sheath-core PLA / PBS composite fiber;
[0069] S4. The obtained core-sheath PLA / PBS composite fibers are dried and cut into core-sheath PLA / PBS composite short fibers; the obtained core-sheath PLA / PBS composite short fibers are mixed with cellulose fibers and formed into a web using a web forming machine to obtain a fiber web, the obtained fiber web is treated with a high-pressure water spunlace machine to obtain a water-spunlace fiber web, and then dried to obtain a degradable water-spunlace non-woven fabric.
[0070] The drying in step S1 is performed by vacuum drying at 65° C. for 12 hours. After drying, the moisture content of the low-melting-point polybutylene succinate (PBS), polyphosphate ester (PPE) and high-melting-point polylactic acid (PLA) pellets is less than 50 PPm.
[0071] In step S1, the low-melting-point polybutylene succinate has a melting point of 105-130°C, and the high-melting-point polylactic acid has a melting point of 155-175°C.
[0072] In the material A of step S2, the mass ratio of low melting point polybutylene succinate to polyphosphate and tributyl citrate is 100:15:5.
[0073] The mass ratio of the high melting point polylactic acid in step S3 to the low melting point polybutylene succinate in material A is 90:90.
[0074] In step S3, the melting temperature of material A is controlled at 135°C; the melting temperature of the high melting point polylactic acid is controlled at 180°C.
[0075] In step S3, the spinning temperature is 170° C. and the winding speed is 700 m / min; the drawing temperature is 60° C. and the drawing multiple is 2.5 times.
[0076] In step S4, the drying is performed at 80° C. with hot air, and the sheath-core PLA / PBS composite short fibers have a length of 30 mm.
[0077] The cellulose fibers in step S4 include cotton fibers.
[0078] The cellulose fibers in step S4 have a fineness of 1.5-4.5 tex and a length of 30 mm.
[0079] The mass ratio of the core-sheath PLA / PBS composite short fibers to the cellulose fibers in step S4 is 7:3.
[0080] The web forming in step S4 is performed by airflow forming with an airflow intensity of 0.5 m / s.
[0081] In step S4, the spunlace is performed at a pressure of 150 bar, the number of spunlaces is 2, and the speed at which the fiber web passes through the spunlace machine is 30 m / min; and the drying is performed by hot air drying at a temperature of 100°C.
[0082] Example 3 Preparation of a degradable spunlace nonwoven fabric capable of ultrasonic bonding:
[0083] S1, taking low melting point polybutylene succinate (PBS) and polyphosphate (PPE), and high melting point polylactic acid (PLA) pellets for drying;
[0084] S2, taking low melting point polybutylene succinate (PBS) and polyphosphate (PPE) and tributyl citrate (TBC) and mixing them evenly to obtain material A;
[0085] S3, melting material A and high melting point polylactic acid (PLA) by two screws of a bicomponent spinning machine respectively, and spinning the two melts through a sheath-core spinning assembly to obtain a sheath-core PLA / PBS composite fiber;
[0086] S4. The obtained core-sheath PLA / PBS composite fibers are dried and cut into core-sheath PLA / PBS composite short fibers; the obtained core-sheath PLA / PBS composite short fibers are mixed with cellulose fibers and formed into a web using a web forming machine to obtain a fiber web, the obtained fiber web is treated with a high-pressure water spunlace machine to obtain a water-spunlace fiber web, and then dried to obtain a degradable water-spunlace non-woven fabric.
[0087] The drying in step S1 is performed by vacuum drying at 65° C. for 8 hours. After drying, the moisture content of the low-melting-point polybutylene succinate (PBS), polyphosphate ester (PPE) and high-melting-point polylactic acid (PLA) pellets is less than 50 PPm.
[0088] In step S1, the low-melting-point polybutylene succinate has a melting point of 105-130°C, and the high-melting-point polylactic acid has a melting point of 155-175°C.
[0089] In the material A described in step S2, the mass ratio of low melting point polybutylene succinate to polyphosphate and tributyl citrate is 80:15:5.
[0090] The mass ratio of the high melting point polylactic acid in step S3 to the low melting point polybutylene succinate in material A is 10:30.
[0091] In step S3, the melting temperature of material A is controlled at 135°C; the melting temperature of the high melting point polylactic acid is controlled at 160°C.
[0092] In step S3, the spinning temperature is 160° C. and the winding speed is 700 m / min; the drawing temperature is 60° C. and the drawing multiple is 2.5 times.
[0093] In step S4, the drying is performed at 80° C. with hot air, and the sheath-core PLA / PBS composite short fibers have a length of 30 mm.
[0094] In step S4, the cellulose fibers are wrapped with cotton fibers.
[0095] The cellulose fibers in step S4 have a fineness of 1.5-4.5 tex and a length of 30 mm.
[0096] The mass ratio of the core-sheath PLA / PBS composite short fibers to the cellulose fibers in step S4 is 7:3.
[0097] The web forming in step S4 is performed by airflow forming with an airflow intensity of 0.8 m / s.
[0098] In step S4, the spunlace is performed at a pressure of 100 bar, the number of spunlaces is 2, and the speed at which the fiber web passes through the spunlace machine is 10 m / min; and the drying is performed by hot air drying at a temperature of 80°C.
[0099] Example 4 Preparation of a degradable spunlace nonwoven fabric capable of ultrasonic bonding:
[0100] S1, taking low melting point polybutylene succinate (PBS) and polyphosphate (PPE), and high melting point polylactic acid (PLA) pellets for drying;
[0101] S2, taking low melting point polybutylene succinate (PBS) and polyphosphate (PPE) and tributyl citrate (TBC) and mixing them evenly to obtain material A;
[0102] S3, melting material A and high melting point polylactic acid (PLA) by two screws of a bicomponent spinning machine respectively, and spinning the two melts through a sheath-core spinning assembly to obtain a sheath-core PLA / PBS composite fiber;
[0103] S4. The obtained core-sheath PLA / PBS composite fibers are dried and cut into core-sheath PLA / PBS composite short fibers; the obtained core-sheath PLA / PBS composite short fibers are mixed with cellulose fibers and formed into a web using a web forming machine to obtain a fiber web, the obtained fiber web is treated with a high-pressure water spunlace machine to obtain a water-spunlace fiber web, and then dried to obtain a degradable water-spunlace non-woven fabric.
[0104] The drying in step S1 is performed by vacuum drying at 65° C. for 8 hours. After drying, the moisture content of the low-melting-point polybutylene succinate (PBS), polyphosphate ester (PPE) and high-melting-point polylactic acid (PLA) pellets is less than 50 PPm.
[0105] In step S1, the low-melting-point polybutylene succinate has a melting point of 105-130°C, and the high-melting-point polylactic acid has a melting point of 155-175°C.
[0106] In the material A described in step S2, the mass ratio of low melting point polybutylene succinate to polyphosphate and tributyl citrate is 80:15:5.
[0107] The mass ratio of the high melting point polylactic acid in step S3 to the low melting point polybutylene succinate in material A is 10:30.
[0108] In step S3, the melting temperature of material A is controlled at 135°C; the melting temperature of the high melting point polylactic acid is controlled at 160°C.
[0109] In step S3, the spinning temperature is 160° C. and the winding speed is 700 m / min; the drawing temperature is 90° C. and the drawing multiple is 2.5 times.
[0110] In step S4, the drying is performed by hot air drying at 100° C., and the sheath-core PLA / PBS composite short fibers have a length of 30 mm.
[0111] In step S4, the cellulose fibers are wrapped with cotton fibers.
[0112] The cellulose fibers in step S4 have a fineness of 1.5-4.5 tex and a length of 40 mm.
[0113] In step S4, the mass ratio of the core-sheath PLA / PBS composite short fibers to the cellulose fibers is 1.25:5.
[0114] The web forming in step S4 is performed by airflow forming with an airflow intensity of 0.8 m / s.
[0115] In step S4, the spunlace is performed at a pressure of 100 bar, the number of spunlaces is 2, and the speed at which the fiber web passes through the spunlace machine is 10 m / min; and the drying is performed by hot air drying at a temperature of 80°C.
[0116] The difference between Comparative Example 1 and Example 3 is that material A does not include polyphosphate (PPE)
[0117] S1, taking low melting point polybutylene succinate (PBS) and high melting point polylactic acid (PLA) pellets for drying;
[0118] S2, taking low melting point polybutylene succinate (PBS) and tributyl citrate (TBC) and mixing them evenly to obtain material A;
[0119] S3, melting material A and high melting point polylactic acid (PLA) by two screws of a bicomponent spinning machine respectively, and spinning the two melts through a sheath-core spinning assembly to obtain a sheath-core PLA / PBS composite fiber;
[0120] S4. The obtained core-sheath PLA / PBS composite fibers are dried and cut into core-sheath PLA / PBS composite short fibers; the obtained core-sheath PLA / PBS composite short fibers are mixed with cellulose fibers and formed into a web using a web forming machine to obtain a fiber web, the obtained fiber web is treated with a high-pressure water spunlace machine to obtain a water-spunlace fiber web, and then dried to obtain a degradable water-spunlace non-woven fabric.
[0121] The drying in step S1 is performed by vacuum drying at 65° C. for 8 hours. After drying, the moisture content in the low-melting-point polybutylene succinate (PBS) and high-melting-point polylactic acid (PLA) pellets is less than 50 PPm.
[0122] In step S1, the low-melting-point polybutylene succinate has a melting point of 105-130°C, and the high-melting-point polylactic acid has a melting point of 155-175°C.
[0123] In the material A described in step S2, the mass ratio of low melting point polybutylene succinate to tributyl citrate is 80:5.
[0124] The mass ratio of the high melting point polylactic acid in step S3 to the low melting point polybutylene succinate in material A is 10:30.
[0125] In step S3, the melting temperature of material A is controlled at 135°C; the melting temperature of the high melting point polylactic acid is controlled at 160°C.
[0126] In step S3, the spinning temperature is 160° C. and the winding speed is 700 m / min; the drawing temperature is 60° C. and the drawing multiple is 2.5 times.
[0127] In step S4, the drying is performed at 80° C. with hot air, and the sheath-core PLA / PBS composite short fibers have a length of 30 mm.
[0128] In step S4, the cellulose fibers are wrapped with cotton fibers.
[0129] The cellulose fibers in step S4 have a fineness of 1.5-4.5 tex and a length of 30 mm.
[0130] The mass ratio of the core-sheath PLA / PBS composite short fibers to the cellulose fibers in step S4 is 7:3.
[0131] The web forming in step S4 is performed by airflow forming with an airflow intensity of 0.8 m / s.
[0132] In step S4, the spunlace is performed at a pressure of 100 bar, the number of spunlaces is 2, and the speed at which the fiber web passes through the spunlace machine is 10 m / min; and the drying is performed by hot air drying at a temperature of 80°C.
[0133] The difference between Comparative Example 2 and Example 3 is that material A does not contain tributyl citrate (TBC)
[0134] S1, taking low melting point polybutylene succinate (PBS) and polyphosphate (PPE), and high melting point polylactic acid (PLA) pellets for drying;
[0135] S2, taking low melting point polybutylene succinate (PBS) and polyphosphate ester (PPE) and mixing them evenly to obtain material A;
[0136] S3, melting material A and high melting point polylactic acid (PLA) by two screws of a bicomponent spinning machine respectively, and spinning the two melts through a sheath-core spinning assembly to obtain a sheath-core PLA / PBS composite fiber;
[0137] S4. The obtained core-sheath PLA / PBS composite fibers are dried and cut into core-sheath PLA / PBS composite short fibers; the obtained core-sheath PLA / PBS composite short fibers are mixed with cellulose fibers and formed into a web using a web forming machine to obtain a fiber web, the obtained fiber web is treated with a high-pressure water spunlace machine to obtain a water-spunlace fiber web, and then dried to obtain a degradable water-spunlace non-woven fabric.
[0138] The drying in step S1 is performed by vacuum drying at 65° C. for 8 hours. After drying, the moisture content of the low-melting-point polybutylene succinate (PBS), polyphosphate ester (PPE) and high-melting-point polylactic acid (PLA) pellets is less than 50 PPm.
[0139] In step S1, the low-melting-point polybutylene succinate has a melting point of 105-130°C, and the high-melting-point polylactic acid has a melting point of 155-175°C.
[0140] In the material A described in step S2, the mass ratio of low melting point polybutylene succinate to polyphosphate is 80:15.
[0141] The mass ratio of the high melting point polylactic acid in step S3 to the low melting point polybutylene succinate in material A is 10:30.
[0142] In step S3, the melting temperature of material A is controlled at 135°C; the melting temperature of the high melting point polylactic acid is controlled at 160°C.
[0143] In step S3, the spinning temperature is 160° C. and the winding speed is 700 m / min; the drawing temperature is 60° C. and the drawing multiple is 2.5 times.
[0144] In step S4, the drying is performed at 80° C. with hot air, and the sheath-core PLA / PBS composite short fibers have a length of 30 mm.
[0145] In step S4, the cellulose fibers are wrapped with cotton fibers.
[0146] The cellulose fibers in step S4 have a fineness of 1.5-4.5 tex and a length of 30 mm.
[0147] The mass ratio of the core-sheath PLA / PBS composite short fibers to the cellulose fibers in step S4 is 7:3.
[0148] The web forming in step S4 is performed by airflow forming with an airflow intensity of 0.8 m / s.
[0149] In step S4, the spunlace is performed at a pressure of 100 bar, the number of spunlaces is 2, and the speed at which the fiber web passes through the spunlace machine is 10 m / min; and the drying is performed by hot air drying at a temperature of 80°C.
[0150] The difference between Comparative Example 3 and Example 3 is that material A does not include polyphosphate (PPE) and tributyl citrate (TBC).
[0151] Preparation of a degradable spunlace nonwoven fabric capable of ultrasonic bonding:
[0152] S1, taking low melting point polybutylene succinate (PBS) and high melting point polylactic acid (PLA) pellets for drying;
[0153] S2, taking low melting point polybutylene succinate (PBS) as material A;
[0154] S3, melting material A and high melting point polylactic acid (PLA) by two screws of a bicomponent spinning machine respectively, and spinning the two melts through a sheath-core spinning assembly to obtain a sheath-core PLA / PBS composite fiber;
[0155] S4. The obtained core-sheath PLA / PBS composite fibers are dried and cut into core-sheath PLA / PBS composite short fibers; the obtained core-sheath PLA / PBS composite short fibers are mixed with cellulose fibers and formed into a web using a web forming machine to obtain a fiber web, the obtained fiber web is treated with a high-pressure water spunlace machine to obtain a water-spunlace fiber web, and then dried to obtain a degradable water-spunlace non-woven fabric.
[0156] The drying in step S1 is performed by vacuum drying at 65° C. for 8 hours. After drying, the moisture content of the low-melting-point polybutylene succinate (PBS) and high-melting-point polylactic acid (PLA) pellets is less than 50 PPm.
[0157] In step S1, the low-melting-point polybutylene succinate has a melting point of 105-130°C, and the high-melting-point polylactic acid has a melting point of 155-175°C.
[0158] The mass ratio of the high melting point polylactic acid to material A in step S3 is 10:30.
[0159] In step S3, the melting temperature of material A is controlled at 135°C; the melting temperature of the high melting point polylactic acid is controlled at 160°C.
[0160] In step S3, the spinning temperature is 160° C. and the winding speed is 700 m / min; the drawing temperature is 60° C. and the drawing multiple is 2.5 times.
[0161] In step S4, the drying is performed at 80° C. with hot air, and the sheath-core PLA / PBS composite short fibers have a length of 30 mm.
[0162] In step S4, the cellulose fibers are wrapped with cotton fibers.
[0163] The cellulose fibers in step S4 have a fineness of 1.5-4.5 tex and a length of 30 mm.
[0164] The mass ratio of the core-sheath PLA / PBS composite short fibers to the cellulose fibers in step S4 is 7:3.
[0165] The web forming in step S4 is performed by airflow forming with an airflow intensity of 0.8 m / s.
[0166] In step S4, the spunlace is performed at a pressure of 100 bar, the number of spunlaces is 2, and the speed at which the fiber web passes through the spunlace machine is 10 m / min; and the drying is performed by hot air drying at a temperature of 80°C.
[0167] The samples prepared in the above examples and comparative examples were subjected to the following tests:
[0168] 1. Tensile strength test: GB / T 24218.2-2018 "Textile nonwoven fabric test methods Part 2: Determination of breaking strength and breaking elongation"
[0169] Test method: Use a tensile tester to test. Sampling: According to standard size (50mm wide specimen). Test speed: 300mm / min. Test direction: Longitudinal and transverse directions.
[0170] Test results: record the maximum tensile strength (N) and the corresponding elongation at break (%).
[0171] 2. Tear strength test: GB / T 3917.3-2009 "Tear properties of textile fabrics Part 3: Single tongue tearing method"
[0172] Test method: Use a tear strength tester (Elmendorf tear tester). Sampling: According to standard size (100mm x 63mm sample). Test direction: Longitudinal and transverse directions respectively.
[0173] Test results: record the tear strength (N).
[0174] 3. Ultrasonic welding strength test: GB / T 24218.3-2018 "Textile nonwoven fabric test methods Part 3: Determination of ultrasonic welding strength"
[0175] Test method: Use an ultrasonic welding strength tester. Sampling: Place the cut non-woven fabric samples in the welding area of the ultrasonic welding machine according to the standard size (25mm wide sample). Make sure that the two samples are stacked on top of each other and the contact surfaces are neatly aligned. Start the ultrasonic welding machine to make the two layers of non-woven fabric generate heat through high-frequency vibration to achieve the welding effect. The frequency is 30kHz and the welding time is 1 second. After welding is completed, let the sample cool to room temperature to ensure that the bonding strength of the welding area reaches a stable state. Test speed: 300mm / min.
[0176] Test results: record the maximum welding strength (N / 25mm). See Table 1 for the test results.
[0177] Table 1 Sample performance test results
[0178]
[0179]
[0180] In the prior art, PPE is mainly used as a flame retardant to improve the flame retardant properties of materials, while TBC improves the flexibility and processing properties of materials through plasticizing modification, and there is no report on the application of the second two to PBS to improve the performance of materials. In the present invention, it can be seen from the above results that the specific formula provided by the present invention effectively suppresses the phenomenon of non-woven fabric fuzzing and significantly improves the mechanical properties of non-woven fabrics. PPE may form hydrogen bonds or ionic bonds with hydroxyl or carboxyl groups on the PBS molecular chain through its phosphate group, thereby enhancing the interaction force between molecules, making the overall structure of the composite material more compact, and then improving tensile strength and tear strength; PPE may also play the role of a nucleating agent, promoting the crystallization of PBS and forming a more complete crystal structure, which also helps to improve the strength and toughness of the material. As a plasticizer, TBC may be inserted between the PBS molecular chains to increase the mobility of the chain segments, thereby reducing the rigidity of the material to a certain extent and improving flexibility. However, in this composite system, an appropriate amount of TBC may reduce the friction and wear between fibers through its intermolecular lubrication, thereby reducing the generation of burrs. TBC may also promote the compatibility between PBS and PLA to a certain extent, making the skin-core structure more stable, reducing interface defects, and thus improving the overall performance of the composite fiber. The addition of PPE and TBC may improve the surface properties of PBS, making it easier to form a strong bond with other materials during ultrasonic welding. In particular, the phosphate group of PPE may enhance the interaction force between the interfaces, while the plasticizing effect of TBC may contribute to the close fit of the welding interface. The skin-core structure of the composite fiber may also contribute to the ultrasonic welding strength. PLA as the skin layer may provide good rigidity and wear resistance, while PBS as the core layer provides good flexibility and processing performance. This structure may be easier to form a uniform welding interface during ultrasonic welding, thereby improving the welding strength.
[0181] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
[0182] The present invention and its implementation methods are described above, which is not restrictive and is only one of the implementation methods of the present invention. The actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.
Claims
1. A method for preparing a degradable spunlace nonwoven fabric capable of ultrasonic bonding, characterized in that: The following steps are involved: S1, taking low melting point polybutylene succinate, polyphosphate and high melting point polylactic acid pellets and drying them; S2, taking low melting point polybutylene succinate, polyphosphate and tributyl citrate and mixing them evenly to obtain material A; S3, material A and high melting point polylactic acid are melted separately by two screws of a two-component spinning machine, and the two melts are spun through a sheath-core spinning assembly to obtain a sheath-core PLA / PBS composite fiber; S4, drying the obtained PLA / PBS composite fiber and cutting it into PLA / PBS composite short fiber; The obtained skin-core PLA / PBS composite short fibers are mixed with cellulose fibers and formed into a web using a web forming machine to obtain a fiber web. The obtained fiber web is treated with a high-pressure water spunlace machine to obtain a spunlace fiber web, which is then dried to obtain a degradable spunlace nonwoven fabric.
2. The method for preparing a degradable spunlace nonwoven fabric capable of ultrasonic bonding according to claim 1, characterized in that: The drying in step S1 is performed by vacuum drying at 45-65° C. for 8-12 hours. After drying, the moisture content of the low-melting-point polybutylene succinate, polyphosphate and high-melting-point polylactic acid pellets is less than 50 PPm.
3. The method for preparing a degradable spunlace nonwoven fabric capable of ultrasonic bonding according to claim 1, characterized in that: In step S1, the low-melting-point polybutylene succinate has a melting point of 105-130°C, and the high-melting-point polylactic acid has a melting point of 155-175°C.
4. The method for preparing a degradable spunlace nonwoven fabric capable of ultrasonic bonding according to claim 1, characterized in that: In the material A described in step S2, the mass ratio of low melting point polybutylene succinate to polyphosphate and tributyl citrate is (80-100):(10-15):(3-5).
5. The method for preparing a degradable spunlace nonwoven fabric capable of ultrasonic bonding according to claim 1, characterized in that: The mass ratio of the high melting point polylactic acid in step S3 to the low melting point polybutylene succinate in material A is (10-90):(10-90).
6. The method for preparing a degradable spunlace nonwoven fabric capable of ultrasonic bonding according to claim 1, characterized in that: In step S3, the melting temperature of material A is controlled at 110-135°C; the melting temperature of the high melting point polylactic acid is controlled at 160-180°C.
7. The method for preparing a degradable spunlace nonwoven fabric capable of ultrasonic bonding according to claim 1, characterized in that: In step S3, the spinning temperature is 155-170° C., the winding speed is 700-1300 m / min; the drawing temperature is 60-90° C., and the drawing multiple is 2.5-4.5 times.
8. The method for preparing a degradable spunlace nonwoven fabric capable of ultrasonic bonding according to claim 1, characterized in that: The drying in step S4 is performed by hot air drying at 80-130° C., and the length of the core-skin PLA / PBS composite short fibers is 3-100 mm.
9. The method for preparing a degradable spunlace nonwoven fabric capable of ultrasonic bonding according to claim 1, characterized in that: The cellulose fibers described in step S4 include one or more of viscose fibers, cotton, linen, bamboo fibers, and regenerated cellulose fibers; the cellulose fibers described in step S4 have a length of 30-50 mm; the mass ratio of the core-sheath PLA / PBS composite short fibers to the cellulose fibers described in step S4 is (1.25-7):(3-5).
10. The method for preparing a degradable spunlace nonwoven fabric capable of ultrasonic bonding according to claim 1, characterized in that: The web forming in step S4 is performed by airflow forming with an airflow intensity of 0.5-1.0 m / s; the hydroentanglement in step S4 is performed with a pressure of 80-150 bar, 2-4 times of hydroentanglement, and the speed of the fiber web passing through the hydroentanglement machine is 10-30 m / min; the drying is performed by hot air drying at a temperature of 80-100°C.
Citation Information
Patent Citations
Biodegradable two-component low-melting point composite fiber
CN102191587A
Production method of bio-degradable heat-viscose bi-component filament fiber
CN102560709A
PLA mixed cotton spunlace filler and production process thereof
CN114808273A
Polylactic acid short fiber, method for producing the same and nonwoven fabric
JP2006200085A
